Surgical Treatment of Morbid Obesity - Chang Min Lee; Jong-Han Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Surgical therapy is currently the only effective treatment for morbid obesity. Bariatric surgery traditionally consisted of laparoscopic gastric bypass and adjustable gastric banding in numerous patients. Recently, laparoscopic sleeve gastrectomy has become the most common bariatric procedure performed. Publicly issued medical-accident had a critical effect on the incidence and trend of bariatric surgery in Korea. Recently, the trend of bariatric surgery has shifted from weight loss surgery to metabolic surgery. The onco-metabolic surgical concept needs to be considered for gastric cancer patients with type II diabetes mellitus (DM) who are expecting a favorable prognosis. Therefore, for gastric cancer patients with type II DM, curative gastrectomy with long-limb bypass reconstruction could be a more attractive option for long-term diabetes control. Although a few centers are currently applying this reconstruction method for some early gastric cancer cases, further studies are needed.